Disney's winnie the pooh: the most grand adventure - Milne, A. A. (Ladybird London, 1999)
Christopher Robin has disappeared, leaving Winnie the Pooh a note saying he has gone to Skull! Join Pooh and friends as they set off on a grand adventure to rescue their very best friend.